Influence of Socio-Demographic Characteristics on Academic Performance of Medical Students - Salahuddin, Sheikh; Talukder, Md Humayun Kabir (Bangladesh Journal of Medical Education, 2017)
This descriptive cross sectional study was conducted to explore the influence of socio-demographic characteristics on academic performance of medical students. The study period was from July 2015 to June 2016. Total 627 final year MBBS students of 11 (6 government and 5 non-government) medical colleges were selected through convenient sampling technique. A self-administered semi structured questionnaire and an interview schedule were used. Study revealed that family income did not have any influence on the academic performance of medical students. Location of parental stay did not show any influence on students' academic performance. Respondents' previous medium of study had little influence on their academic performance. Students who were regular in passing formative assessment also had better performance in professional examinations. Students who failed in professional examinations mostly failed in oral portions (more than 80%). Father's educational qualification did not have any influence on the performance of students but mother's educational qualification had positive relation on it. Performance of those students who were willing to study MBBS were better than unwilling ones. Respondents who were satisfied with the money provided by the parents/guardians were more regular in passing professional examinations. Many of the findings of this study are aligned with findings of the study conducted by Ali S, Haider Z et al.1 Bangladesh Journal of Medical Education Vol.8(2) 2017: 18-23